Excited delirium syndrome. (2nd March 2022) - Sengstock, Brian; Curtis, Janet
Abstract : Excited delirium syndrome involves extreme agitation and aggression in a patient with an altered mental status; around one in ten cases ends in cardiac arrest. It has two main triggers: acute drug use and psychiatric illness. Patients display violent behaviour, increased pain tolerance and great strength; they pose significant risks to themselves and those around them. Maintaining safety on scene is paramount, which can be supported by a dual response by paramedics and law enforcement officers, and the patient is likely to need restraining or sedation. Treatment is non-specific and involves managing symptoms and complications such as hyperthermia, acidosis and rhabdomyolysis.